Author Correction: A systems pharmacology approach to identify the autophagy‑inducing effects of Traditional Persian medicinal plants - Pouria Mosaddeghi (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.